PENINGKATAN HASIL BELAJAR KPK DAN FPB DENGAN PENDEKATAN KONTRUKTIVISME DI SDN 05 PASAR BARU - Yusmaleni, Yeni; Masniladevi, Masniladevi; Zen, Mulyani (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
This study is aimed at improving the students' learning outcomes in Math in grade IV of SDN No. 05 Pasar Baru Bayang through the implementation of the constructivism approach. The result of the RPP evaluation shows that there is an increase in the students' learning outcomes from approximately 81% in cycle one to 89% in cycle two. Evaluation on the teachers' activities reveals that the scores improved from 75% in cycle one to 89% in cycle two. Evaluation on the students' activities improved from 73% in cycle one to 89% in cycle two. Thus, it can be concluded that the constructivism approach works well in improving the students' learning outcomes in Math.  Kata kunci : hasil, pembelajaran matematika, pendekatan kontruktivisme